Acceptance and Perception of Teachers and Students Regarding the Appropriateness of Using AI Chatbots in the Classroom - Abiodun, T. O Abiodun, T. O; Chinaka, T.W Chinaka, T.W; Asanre, A. A Asanre, A. A; Siphokazi, V Siphokazi, V (FKIP - Universitas Riau, 2026)
This study examined the acceptance and perception of teachers and learners regarding the appropriateness of using AI chatbots in the classroom. Using a descriptive survey research approach, the study was carried out. The sample for the study consisted of 384 randomly chosen respondents, 24 teachers, and 360 students in six (6) secondary schools from three (3) local government in Ogun State, Nigeria. This study used simple random sampling as its sampling technique. Data was gathered using a structured questionnaire called